Hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone and preparation method of hollow fiber ultrafiltration membrane
By blending polyarylether sulfone with polyether sulfone with ion pairs, a hollow fiber ultrafiltration membrane with gradient pore size distribution is formed, which solves the problem of poor compatibility of hydrophilic substances and improves the anti-pollution performance and blood compatibility of the membrane.
Patent Information
- Application Number
- CN202510593820.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-08
AI Technical Summary
During the preparation process of existing polyethersulfone hemodialysis membranes, hydrophilic substances have poor compatibility with the membrane body, and the distribution of hydrophilic substances in the membrane pores is less, resulting in a decrease in anti-pollution performance.
Ion pair-modified polyarylether sulfone is blended with polyether sulfone, and the three-axis microfluidic spinning technology and non-solvent-induced phase separation are formed to form a hollow fiber ultrafiltration membrane with gradient pore size distribution, combining the electrostatic interaction between sulfonic acid groups and quaternary ammonium groups to form a stable three-dimensional network structure.
It improves the hydrophilicity and stability of the membrane, enhances the ability to remove small molecule toxins, extends the service life of the membrane, and reduces the risk of thrombosis.
Smart Images

Figure CN120437848A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of separation membranes, specifically to the field of hemodialysis membranes, and in particular to a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone and a preparation method thereof. Background Art
[0002] Hemodialysis is a key renal replacement therapy for patients with acute and chronic renal failure. It works by draining the patient's blood and passing it through a dialyzer composed of hollow fiber membranes. The concentration gradient and pressure difference formed on the inside and outside of the membrane drive the exchange of substances between the blood and the dialysate through multiple mass transfer mechanisms, including diffusion, convection, adsorption, and ultrafiltration. During this process, metabolic waste products (such as urea and creatinine) and excess electrolytes are efficiently removed, while acid-base balance and fluid volume are regulated. As the core functional unit of the dialyzer, the ideal hollow fiber membrane must meet multi-dimensional performance requirements: (i) biosafety, avoiding the risk of thrombosis or immune response caused by the dissolution of the polymer matrix or additives; (ii) mechanical stability, withstanding long-term transmembrane pressure and shear force and maintaining an intact porous structure; and (iii) precise separation efficiency, with the ability to selectively screen medium and large molecular proteins (such as albumin, 66 kDa) while ensuring efficient removal of small molecule toxins (<500 Da) (Journal of Industrial and Engineering Chemistry 139(2024)94–110).
[0003] Polyaryl ether sulfone (PAES), such as polysulfone and polyethersulfone, are used in the biomedical field due to their excellent chemical stability, good mechanical strength and high temperature resistance. Among them, polyethersulfone (PES) is widely used as a hollow fiber membrane material for hemodialysis, but its inherent hydrophobicity leads to the following problems: it easily adsorbs biological molecules such as proteins and lipids in the blood, forming a "secondary membrane" that blocks the membrane pores, reducing flux and toxin clearance efficiency; it triggers adverse blood compatibility issues such as complement activation and coagulation reactions, increasing the risk of patient treatment (Journal of Membrane Science 657(2022)120680). Compared with traditional hydrophilic modification, although blending hydrophilic additives (such as PVP and PEG) can improve hydrophilicity in the short term, small molecules are easily precipitated from the matrix, resulting in poor long-term stability, and the precipitates may cause allergies or coagulation. Surface modification (such as grafting and coating) processes are relatively complex and may damage the membrane pore structure. The surface modification layer is easy to fall off and is difficult to maintain for a long time. The existing technology urgently needs a modification strategy that is both well compatible with the PES matrix and can achieve hydrophilic-hydrophobic synergy, so as to take into account anti-protein adsorption, long-term stability and high permeability (Journal of Industrial and Engineering Chemistry 138(2024)72–103).
[0004] Ion-pair (anionic and cationic) modified polymers have unique advantages for use as hemodialysis membranes (Chinese Journal of Chemical Engineering 49(2022)100–110). Ion-pair polymers usually contain polar or charged groups (such as sulfonic acid groups, quaternary ammonium groups, etc.), which can significantly improve the hydrophilicity of the PES membrane surface. They can reduce the adsorption of proteins in the blood (such as albumin and fibrinogen) on the membrane surface, reduce membrane fouling, and extend the service life. They can improve the permeation efficiency during dialysis and maintain a stable ultrafiltration rate. Ion-pair polymers can reduce the activation of blood components by regulating the surface charge or introducing biomimetic groups (such as phospholipid analogs). They can reduce platelet adhesion and complement activation, reducing the risk of thrombosis. They can inhibit the excessive activation of white blood cells (such as neutrophils) and reduce the inflammatory response. The electrostatic interaction of ion-pair polymers can regulate the phase separation process of PES and optimize the membrane pore size distribution. They can selectively remove small molecule toxins (such as urea and creatinine) while retaining medium molecule beneficial substances (such as albumin). Enhance the clearance capacity of specific charged toxins (such as β2-microglobulin) through charge repulsion effect. Improve patient tolerance during dialysis and reduce complications (such as hypotension and allergic reactions). Negatively charged groups (such as sulfonic acid groups) in ion-pair polymers can inhibit the adsorption of coagulation factors (such as prothrombin) through electrostatic repulsion. Reduce the dosage of heparin and reduce the risk of bleeding in patients. Extend the service life of the dialyzer and reduce the need for frequent replacement. Ion-pair polymers are modified by blending or grafting with PES to retain the original high mechanical strength and high temperature and chemical corrosion resistance of PES.
[0005] Ion-pair polymer modification and process innovation are important approaches to address the poor blood compatibility and contamination issues associated with the hydrophobic nature of traditional PES hollow fiber ultrafiltration membranes. Further exploration is needed to design novel amphiphilic copolymers (e.g., block and star structures) to develop novel hemodialysis membranes with precise separation capabilities for medium and large molecules in blood, stable performance, and simple preparation methods. This approach could better meet the needs of hemodialysis and be suitable for industrial production. Summary of the Invention
[0006] In order to solve the above-mentioned technical problems existing in the prior art, the purpose of the present invention is to provide a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone to solve the problems of poor compatibility between hydrophilic substances and the membrane body during the preparation process, less distribution of hydrophilic substances in the membrane pores, and loss of hydrophilic substances during the use of the anti-fouling membrane, resulting in a decrease in anti-fouling performance.
[0007] To achieve the above objectives, the present invention provides a first aspect of a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone and a preparation method thereof, comprising the following steps:
[0008] (1) Preparation of ion-pair modified poly(arylethersulfone)
[0009] (1) A certain amount of 2-(3-(dimethylamino)propane)-3,3-bis(4-hydroxyphenyl)isoindolinone monomer, 4,4'-dihydroxydiphenyl sulfone monomer and 4,4'-difluorodiphenyl sulfone monomer were weighed and added to N,N'-dimethylacetamide (DMAc). The temperature was programmed to 160°C, potassium carbonate was used as a catalyst, and the temperature was maintained for 18 hours in a nitrogen atmosphere to obtain polyarylethersulfone (PAES) (Formula I), wherein 2-(3-(dimethylamino)propane)-3,3-bis(4-hydroxyphenyl)isoindolinone monomer, 4,4'-dihydroxydiphenyl sulfone monomer and 4,4'-difluorodiphenyl sulfone monomer were weighed and added to N,N'-dimethylacetamide (DMAc). The temperature was programmed to 160°C, potassium carbonate was used as a catalyst, and the temperature was maintained for 18 hours. Polyarylethersulfone (PAES) (Formula I) was obtained by co-condensation. The ratio of the total amount of 3'-bis(4-hydroxyphenyl)isoindolinone and 4,4'-dihydroxydiphenyl sulfone monomers to the amount of 4,4'-difluorodiphenyl sulfone is 1:1, the molar ratio of the 2-(3-(dimethylamino)propane)-3,3'-bis(4-hydroxyphenyl)isoindolinone monomer and the 4,4'-dihydroxydiphenyl sulfone monomer is x:100-x=90%~50%:10%~50%; the number average molecular weight Mn of the PAES-x is 30,000~120,000.
[0010]
[0011] (2) dissolving the polyarylethersulfone (PAES-x) prepared in step (1) in an organic solvent, and then adding sodium 3-bromopropanesulfonate at a mass ratio of 10:1.0 to 2.0 based on the oligomer, stirring for a certain period of time, precipitating in a precipitant, and vacuum drying to obtain an ion-pair modified polyarylethersulfone (iPAES-x) (Formula II);
[0012]
[0013] (2) Preparation of homogeneous casting solution
[0014] First, add the solvent and porogen into the reactor and stir. Then add PES and iPAES-x prepared in step (1) into the reactor. The feeding ratio is as follows:
[0015]
[0016]
[0017] A certain amount of polyethersulfone (PES), ion-pair modified polyarylethersulfone (iPAES-x), porogen, non-solvent and solvent were weighed respectively, and then each component was placed in a batching container in turn, and fully stirred and dissolved in the temperature range of 20-110°C for 3-12 hours until a homogeneous solution was formed. After filtering through a stainless steel filter, vacuum or standing for degassing for 6-24 hours, it was left to mature to obtain a casting solution.
[0018] Preferably, the raw materials are weighed in the above steps according to the following weight ratio: 10 to 35 parts of PES, 3 to 15 parts of iPAES-x, 2 to 10 parts of porogen, 0.5 to 15 parts of non-solvent, and 55 to 75 parts of solvent. More preferably, PES is 15 parts, iPAES-x is 10 parts, porogen is 8 parts, non-solvent is 5 parts, and solvent is 62 parts.
[0019] Preferably, the porogen used in the above step is one or more of polyethylene glycol, polyvinyl pyrrolidone, lithium chloride, and polymethyl acrylate, more preferably lithium chloride.
[0020] Preferably, the non-solvent used in the above step is one or more of dipropylene glycol, tetraethylene glycol, and ethylene glycol monomethyl ether, more preferably dipropylene glycol.
[0021] Preferably, the solvent used in the above step is one or more of N,N'-dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), and N-methylpyrrolidone (NMP), more preferably DMAc.
[0022] Preferably, the stirring temperature of the casting solution in the above steps is 20-110° C., and the heating time is 3-12 h, more preferably 70° C. for 6 h.
[0023] Preferably, the standing degassing time in the above steps is 6 to 24 hours, more preferably 12 hours.
[0024] (3) Preparation of hollow fiber membrane
[0025] (1) The ambient temperature and humidity are controlled to be 18-25°C and 20-50 RH%, respectively. The casting solution prepared in step (ii) is extruded through a spinneret using a metering pump, passed through an air bath for 10-120 seconds, and then vertically immersed in a first coagulation bath (DMAC / water: DMAC concentration 40-60%, temperature 25-40°C) at 20-80°C for a phase separation and solidification time of 60-180 seconds. The solution is then immersed in a second coagulation bath (DMAC / water: DMAC concentration 55-70%, temperature 45-80°C) for a phase separation and solidification time of 60-240 seconds, and finally introduced into a fiber collection tank through winding. The core liquid is composed of pure water or an aqueous solution containing an organic solvent with a mass concentration of 5-50%, thereby forming a nascent hollow fiber membrane.
[0026] Preferably, the ambient temperature and humidity in the above steps are 18-25° C. and 20-50 RH%, respectively, and more preferably 25° C. and 40 RH%.
[0027] Preferably, the air bath time in the above steps is 30 to 80 seconds, the first coagulation bath temperature is 20 to 80° C., the DMAC concentration is 10 to 60%, and the phase separation solidification time is 30 to 180 seconds, more preferably 80 seconds, 30° C., 40%, and 120 seconds, respectively.
[0028] Preferably, in the above step, the temperature of the second coagulation bath is 45-80° C., the DMAc concentration is 55-70%, and the phase separation solidification time is 60-240 s, more preferably 50° C., 60%, and 180 s, respectively.
[0029] (2) The hollow fiber ultrafiltration membrane prepared in the above step is immersed in deionized water at 20-40°C for 24-48 hours to set the shape, and rinsed with deionized water to remove residual solvent and additives to form a shaped hollow fiber membrane with an inner and outer diameter of 180-220 μm and 250-350 μm.
[0030] Preferably, the deionized water coagulation bath temperature in the above steps is 20-40° C., and the setting time is 24-48 hours. More preferably, the temperature and setting time are 25° C. and 36 hours, respectively.
[0031] Therefore, the present invention adopts a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone and a preparation method thereof, which has the following beneficial effects:
[0032] (1) Modify polyarylethersulfone by ion pairing to introduce sulfonic acid groups (-SO3H) or quaternary ammonium groups (-NR3 + ), forming a network of ion pairs through hydrogen bonds and electrostatic interactions with the hydrophobic segments of PES. The hydrophilicity of the sulfonic acid groups significantly reduces the membrane contact angle and enhances surface negative charge through pH-responsive ionization, repelling negatively charged proteins (such as albumin). The quaternary ammonium groups inhibit blood cell adhesion through electrostatic repulsion, improving long-term stability.
[0033] (2) Using three-phase in-line microfluidic spinning technology, combined with non-solvent-induced phase separation and ion-pair-induced microphase separation, a gradient pore size distribution with dense outer and sparse inner is formed: the outer dense layer (pore size <6nm) realizes the efficient screening of small molecule toxins (urea, creatinine); the inner macroporous support layer (pore size 50-100nm) ensures mechanical strength and high throughput.
[0034] (3) Using hydrophobic polyethersulfone as the membrane substrate, ion-pair modification of polyarylethersulfone forms microphase separation in the membrane, which helps to form a uniform microstructure and improve the permeability and stability of the membrane. After iPAES is blended with PES, a three-dimensional network structure is formed through ionic cross-linking, which inhibits membrane pore collapse.
[0035] (4) Diffusion-dominated small molecule clearance: The diffusion efficiency of urea (60Da) and creatinine (113Da) is accelerated through hydrophilic channels; adsorption-dominated medium and large molecule clearance: The sulfonic acid group can specifically adsorb β2-microglobulin (11.8kDa), and combined with pore size screening to achieve precise clearance. The data showed that the clearance rate of medium-molecule toxins was >40%. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1a and Figure 1b This is an appearance diagram of the hollow fiber ultrafiltration membrane prepared in Example 1.
[0037] Figure 2 This is the SEM morphology of the hollow fiber ultrafiltration membrane prepared in Example 1. DETAILED DESCRIPTION
[0038] To further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in combination with some specific examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0039] Example 1
[0040] (1) Preparation of ion-paired polyarylethersulfone
[0041] (1) Weigh 240 mmol of 2-(3-(dimethylamino)propyl)-3,3-bis(4-hydroxyphenyl)isoindolinone monomer, 160 mmol of 4,4'-dihydroxydiphenyl sulfone monomer, and 400 mmol of 4,4'-difluorodiphenyl sulfone monomer, respectively, and add them to 1000 mL of N,N'-dimethylacetamide (DMAc). Gradually raise the temperature to 140°C and hold for 6 h, then raise it to 160°C and hold for 12 h. The reaction mixture was maintained for 18 hours in a N2 atmosphere to obtain polyarylethersulfone (PAES) by cocondensation, wherein the ratio of the total amount of 2-(3-(dimethylamino)propane)-3,3'-bis(4-hydroxyphenyl)isoindolinone and 4,4'-dihydroxydiphenylsulfone monomers to the amount of 4,4'-difluorodiphenylsulfone was 1:1, and the molar ratio of the 2-(3-(dimethylamino)propane)-3,3'-bis(4-hydroxyphenyl)isoindolinone monomer to the 4,4'-dihydroxydiphenylsulfone monomer was x:100-x=60:40; the number average molecular weight Mn of the PAES-60 was 83900.
[0042] (2) The polyarylethersulfone (PAES-x) prepared in step (1) is dissolved in an organic solvent, and then sodium 3-bromopropanesulfonate is added at a mass ratio of 10:1.0 to 2.0 based on the oligomer, stirred for a certain period of time, precipitated in a precipitant, and vacuum dried to obtain ion-pair modified polyarylethersulfone (iPAES-60).
[0043] (2) Preparation of homogeneous casting solution
[0044] First, add the solvent and porogen to a reactor and stir. Then, add PES and iPAES from the first step to the reactor in the following ratios: 15 parts PES, 10 parts iPAES-60, 8 parts lithium chloride, 5 parts dipropylene glycol, and 62 parts DMAc. Each component is placed in a mixing vessel and stirred thoroughly at 70°C for 6 hours to form a homogeneous solution. Filter through a stainless steel filter, vacuum degas or allow to stand for 12 hours, and then allow to mature to produce the casting solution.
[0045] (3) Preparation of hollow fiber ultrafiltration membrane
[0046] (1) The ambient temperature and humidity were controlled at 25°C and 40 RH%, respectively. The casting solution was extruded through a spinneret using a metering pump. After passing through an air bath for 80 seconds, it was vertically immersed in a first coagulation bath (DMAc / water: DMAc concentration 40%, temperature 30°C) for phase separation and solidification for 120 seconds. It was then immersed in a second coagulation bath (DMAc / water: DMAc concentration 60%, temperature 50°C) for phase separation and solidification for 180 seconds. Finally, it was wound and introduced into a fiber collection tank. The core liquid was composed of pure water or an aqueous solution containing an organic solvent with a mass concentration of 10%, forming a nascent hollow fiber membrane.
[0047] (2) The hollow fiber ultrafiltration membrane prepared in the above step was immersed in deionized water at 25° C. for 36 hours to set the membrane, and then rinsed with deionized water to remove the residual solvent and additives to form a set hollow fiber membrane.
[0048] (IV) Characterization of hollow fiber ultrafiltration membrane
[0049] Basic property test: see Table 1. Appearance Figure 1a 、 Figure 1b As shown, the SEM morphology is Figure 2 shown.
[0050] Dialysis assembly production: The obtained hollow fiber membrane was gathered and placed in the dialyzer shell. Polyurethane and epoxy resin were used to seal the two ends. After being placed at room temperature for one day, the membrane area was 0.2m 2 Hemodialysis components.
[0051] Filtration performance testing: Ultrafiltration coefficient (Kuf) testing was conducted in accordance with YY 0053-2016, Hemodialysis and Related Therapies; urea clearance was conducted in accordance with YY / T 1493-2016, Concentrates for Hemodialysis and Related Therapies; β2-microglobulin clearance was conducted in accordance with YY / T 0771.3-2020, Medical Devices for Blood Purification—Part 3: Hemodialysis; Biocompatibility testing was conducted in accordance with GB / T 16886.4-2019, Biological Evaluation of Medical Devices—Part 4: Interaction with Blood; and mechanical properties testing was conducted in accordance with YY / T 0661-2017, Medical Devices—Intravascular Catheters—Sterile Single-Use Catheters—Part 5: Hemodialysis Catheters. The test results are shown in Table 1. Coagulation time testing was conducted in accordance with GB / T 16886.4-2019, Biological Evaluation of Medical Devices—Part 4: Interaction with Blood.
[0052] Example 2
[0053] (1) Preparation of ion-paired polyarylethersulfone
[0054] The same preparation process as in Example 1 was adopted, except that:
[0055] The molar ratio of 2-(3-(dimethylamino)propyl)-3,3'-bis(4-hydroxyphenyl)isoindolinone monomer and 4,4'-dihydroxydiphenyl sulfone monomer is x:100-x=70:30, and the specific molar numbers of the raw materials are 280 mmol and 120 mmol, respectively; the number average molecular weight Mn of the PAES-70 is 91600.
[0056] After functionalization with sodium 3-bromopropane sulfonate, ion-pair modified poly(arylethersulfone) (iPAES-60) was obtained.
[0057] (2) Preparation of homogeneous casting solution
[0058] The same configuration process as in Example 1 is adopted.
[0059] (3) Preparation of hollow fiber ultrafiltration membrane
[0060] The same preparation process as in Example 1 was adopted.
[0061] (IV) Characterization of hollow fiber ultrafiltration membrane
[0062] The same characterization process as in Example 1 was adopted.
[0063] The test results are shown in Table 1.
[0064] Example 3
[0065] (1) Preparation of ion-paired polyarylethersulfone
[0066] The same preparation process as in Example 1 was adopted, except that:
[0067] The molar ratio of 2-(3-(dimethylamino)propyl)-3,3'-bis(4-hydroxyphenyl)isoindolinone monomer and 4,4'-dihydroxydiphenyl sulfone monomer is x:100-x=80:20, and the specific molar numbers of the raw materials are 320 mmol and 80 mmol, respectively; the number average molecular weight Mn of the PAES-80 is 88200.
[0068] After functionalization with sodium 3-bromopropane sulfonate, ion-pair modified poly(arylethersulfone) (iPAES-80) was obtained.
[0069] (2) Preparation of homogeneous casting solution
[0070] The same configuration process as in Example 1 is adopted.
[0071] (3) Preparation of hollow fiber ultrafiltration membrane
[0072] The same preparation process as in Example 1 was adopted.
[0073] (IV) Characterization of the hollow fiber ultrafiltration membrane The same characterization process as in Example 1 was used.
[0074] The test results of each embodiment are shown in Table 1.
[0075]
[0076] Table 1. Test results of the membranes.
Claims
1. A method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone, characterized in that The steps include: (1) Preparation of ion-pair modified poly(arylethersulfone) (1) A certain amount of 2-(3-(dimethylamino)propane)-3,3-bis(4-hydroxyphenyl)isoindolinone monomer, 4,4'-dihydroxydiphenyl sulfone monomer and 4,4'-difluorodiphenyl sulfone monomer were weighed and added to N,N'-dimethylacetamide (DMAc). The temperature was programmed to 160°C, potassium carbonate was used as a catalyst, and the temperature was maintained for 18 hours in a nitrogen atmosphere. Polyarylethersulfone PAES-x was obtained by co-condensation, as shown in Formula I, wherein 2-(3-(dimethylamino)propane)-3,3-bis(4-hydroxyphenyl)isoindolinone monomer, 4,4'-dihydroxydiphenyl sulfone monomer and 4,4'-difluorodiphenyl sulfone monomer were added to N,N'-dimethylacetamide (DMAc). The ratio of the total amount of 3'-bis(4-hydroxyphenyl)isoindolinone and 4,4'-dihydroxydiphenyl sulfone monomers to the amount of 4,4'-difluorodiphenyl sulfone is 1:1, the molar ratio of the 2-(3-(dimethylamino)propyl)-3,3'-bis(4-hydroxyphenyl)isoindolinone monomer to the 4,4'-dihydroxydiphenyl sulfone monomer is x:100-x=90%-50%:10%-50%; the number average molecular weight Mn of the PAES-x is 30,000-120,000; (2) dissolving the poly(aryl ether sulfone) PAES-x prepared in step (1) in an organic solvent, and then adding sodium 3-bromopropane sulfonate in a mass ratio of 10:1.0 to 2.0 based on the oligomer, stirring for a certain period of time, precipitating in a precipitant, and vacuum drying to obtain an ion-pair modified poly(aryl ether sulfone) iPAES-x, as shown in Formula II; (2) Preparation of homogeneous casting solution First, add the solvent and porogen into the reactor and stir. Then add PES and iPAES-x prepared in step (1) into the reactor. The feeding ratio is as follows: Fully stir and dissolve at a temperature range of 20 to 110° C. for 3 to 12 hours until a homogeneous solution is formed, filter through a stainless steel filter, vacuum or allow to stand for degassing for 6 to 24 hours, and then allow to mature to obtain a casting solution; (3) Preparation of hollow fiber membrane (1) controlling the ambient temperature and humidity to be 18-25° C. and 20-50 RH%, respectively, extruding the casting solution prepared in step (ii) through a spinneret using a metering pump, passing through an air bath for 10-120 s, vertically immersing the solution in a first coagulation bath at 20-80° C. for phase separation and solidification for 60-180 s, then immersing the solution in a second coagulation bath for phase separation and solidification for 60-240 s, and finally winding the solution into a fiber collection tank, wherein the core liquid is composed of pure water or an aqueous solution containing an organic solvent with a mass concentration of 5-50%, thereby forming a nascent hollow fiber membrane; (2) The hollow fiber membrane obtained in the above step is immersed in deionized water at 20-40° C. for 24-48 hours to set the membrane, and then rinsed with deionized water to remove residual solvent and additives to form a set hollow fiber membrane.
2. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The preferred feed ratio in step (ii) is 15 parts of PES, 10 parts of iPAES-x, 8 parts of porogen, 5 parts of non-solvent, and 62 parts of solvent.
3. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The porogen in step (2) is one or more of polyethylene glycol, polyvinyl pyrrolidone, lithium chloride, and polymethyl acrylate.
4. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The non-solvent in step (2) is one or more of dipropylene glycol, tetraethylene glycol, and ethylene glycol monomethyl ether.
5. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The solvent in step (2) is one or more of N,N'-dimethylacetamide DMAc, N,N'-dimethylformamide DMF, and N-methylpyrrolidone NMP.
6. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The stirring temperature and heating time of the casting solution in step (ii) are preferably 70° C. and 6 h, and the standing degassing time is preferably 12 h.
7. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The ambient temperature and humidity described in sub-step (1) of step (iii) are preferably 25° C. and 40 RH%.
8. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The air bath time in sub-step (1) of step (iii) is 30 to 80 seconds, the first coagulation bath temperature is 20 to 80°C, the DMAC concentration is 10 to 60%, and the phase separation solidification time is 30 to 180 seconds, more preferably 80 seconds, 30°C, 40%, and 120 seconds respectively; The second coagulation bath temperature is 45-80° C., the DMAc concentration is 55-70%, and the phase separation solidification time is 60-240 s, more preferably 50° C., 60%, and 180 s, respectively.
9. The method for preparing a hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone according to claim 1, wherein: The temperature and duration of the deionized water coagulation bath in sub-step (2) of step (iii) are 25° C. and 36 h, respectively.
10. A hollow fiber ultrafiltration membrane for hemodialysis based on polyethersulfone, characterized in that Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polyether sulfone / phthalazinone structure-containing copolyether sulfone blended hollow fiber hemodialysis membrane and preparation method thereof
CN112221361A
Preparation method of monovalent anion selective amphoteric structure ion exchange membrane
CN116120611A
Preparation method of high-connectivity twisted structure-containing alloy hollow fiber ultrafiltration membrane
CN117018878A
Preparation method of high-flux lining enhanced positively charged hollow fiber ultrafiltration membrane for MBR (Membrane Biological Reactor)
CN117046309A